Light‐Directing Omnidirectional Circularly Polarized Reflection from Liquid‐Crystal Droplets1. (8th December 2014) - Fan, Jing; Li, Yannian; Bisoyi, Hari Krishna; Zola, Rafael S.; Yang, Deng‐ke; Bunning, Timothy J.; Weitz, David A.; Li, Quan
Abstract Constructing and tuning self‐organized three‐dimensional (3D) superstructures with tailored functionality is crucial in the nanofabrication of smart molecular devices. Herein we fabricate a self‐organized, phototunable 3D photonic superstructure from monodisperse droplets of one‐dimensional cholesteric liquid crystal (CLC) containing a photosensitive chiral molecular switch with high helical twisting power. The droplets are obtained by a glass capillary microfluidic technique by dispersing into PVA solution that facilitates planar anchoring of the liquid‐crystal molecules at the droplet surface, as confirmed by the observation of normal incidence selective circular polarized reflection in all directions from the core of individual droplet. Photoirradiation of the droplets furnishes dynamic reflection colors without thermal relaxation, whose wavelength can be tuned reversibly by variation of the irradiation time. The results provided clear evidence on the phototunable reflection in all directions.